Learning to Manage and Managing to Learn: Sustaining Freshwater Recreational Fisheries in a Changing Environment. Issue 2 (25th February 2015) - Hansen, Gretchen J. A.; Gaeta, Jereme W.; Hansen, Jonathan F.; Carpenter, Stephen R.
Abstract : Freshwaters are being transformed by multiple environmental drivers, creating uncertainty about future conditions. One way of coping with uncertainty is to manage for resilience to unanticipated events while facilitating learning through adaptive management. We outline the application of these strategies to freshwater recreational fisheries management using a case study in Wisconsin, USA, where black bass (Micropterus spp.) populations are increasing, while Walleye ( Sander vitreus ) populations are decreasing. Managing for heterogeneity in functional groups (e.g., age classes and prey species of sport fishes), fishery objectives, and regulations can increase resilience, although heterogeneity must be balanced with replication to facilitate learning. Monitoring designed to evaluate management objectives and inform about critical uncertainties, when combined with heterogeneity, creates opportunities for adaptive management, another critical resilience strategy. Although barriers exist to implementing resilience strategies, management designed to accommodate uncertainty and illuminate its consequences is needed to maintain critical fisheries in a rapidly changing world.